indonesia Edukasi Vaksin Covid-19 dan Penggunaan Masker Yang Benar Di Desa Uwemanje Dusun III/RT 06 Kecamatan Kinovaro Kabupaten Sigi - Badrun Kalupek; Mawan Setiawan; Ni Luh Ayu Sriani; Khairil Anwar; Yasoda Febri Arini; Jihan Pahira; Nuryani Rauf; Pirdayanti R.Rahim; Oliviana; Karmila H.Kanoli; Siti Nurhaliza; Ni Nyoman (CV. Multi Kreasi Media, 2022)
Coronavirus Disease 2019 (Covid-19) is caused by the novel coronavirus 2019-nCOV which is highly contagious and spreads rapidly and becomes an outbreak throughout the world including Indonesia. One of the efforts recommended by WHO is the prevention of the spread of Covid-19 with the implementation of vaccines and the use of masks properly and appropriately. The purpose of community service activities is to educate people who have not implemented vaccines for vaccines and educate the public how to use masks properly. The location of the activity was held in Uwemanje Dusun III / RT 06 Village. Methods used in the form of lectures, discussions using leaflet media. The result of educational activities is the community that uses masks as much as 60% and the realization of the vaccine community as much as 60%.